Assessment of brain age in posttraumatic stress disorder: Findings from the ENIGMA PTSD and brain age working groups. Issue 1 (14th December 2021) - Clausen, Ashley N.; Fercho, Kelene A.; Monsour, Molly; Disner, Seth; Salminen, Lauren; Haswell, Courtney C.; Rubright, Emily Clarke; Watts, Amanda A.; Buckley, M. Nicole; Maron‐Katz, Adi; Sierk, Anika; Manthey, Antje; et al.
Abstract: Background: Posttraumatic stress disorder (PTSD) is associated with markers of accelerated aging. Estimates of brain age, compared to chronological age, may clarify the effects of PTSD on the brain and may inform treatment approaches targeting the neurobiology of aging in the context of PTSD. Method: Adult subjects ( N  = 2229; 56.2% male) aged 18–69 years (mean = 35.6, SD = 11.0) from 21 ENIGMA‐PGC PTSD sites underwent T1‐weighted brain structural magnetic resonance imaging, and PTSD assessment (PTSD+, n  = 884). Previously trained voxel‐wise (brainageR) and region‐of‐interest (BARACUS and PHOTON) machine learning pipelines were compared in a subset of control subjects ( n  = 386). Linear mixed effects models were conducted in the full sample (those with and without PTSD) to examine the effect of PTSD on brain predicted age difference (brain PAD; brain age − chronological age) controlling for chronological age, sex, and scan site. Results: BrainageR most accurately predicted brain age in a subset ( n  = 386) of controls (brainageR: ICC = 0.71, R  = 0.72, MAE = 5.68; PHOTON: ICC = 0.61, R  = 0.62, MAE = 6.37; BARACUS: ICC = 0.47, R  = 0.64, MAE = 8.80). Using brainageR, a three‐way interaction revealed that young males with PTSD exhibited higher brain PAD relative to male controls in young and old age groups; old males with PTSD exhibited lower brain PAD compared to male controls of all ages. Discussion: Differential impact of PTSD on brain PAD in younger versus older males may indicate a critical window when PTSD impacts brain aging, followed by age‐related brain changes that are consonant with individuals without PTSD. Future longitudinal research is warranted to understand how PTSD impacts brain aging across the lifespan. Abstract : Posttraumatic stress disorder (PTSD) is associated with markers of accelerated aging. We explored estimates of brain age, as compared to chronological age, as a possible marker of accelerated aging in PTSD populations leveraging a large multi‐site sample. We identified an interaction of PTSD, age, and sex which showed young males with PTSD had a greater brain predicted age difference [PAD] than young male controls, young females with PTSD, and young females without PTSD. A similar pattern was present in middle‐aged males, but the effect of PTSD was weaker than in young adults. Male controls in the old subgroup exhibited higher brain‐PAD than old males with PTSD, old females with PTSD, and old females without PTSD.